Mouse models for mesothelioma drug discovery and development. (3rd June 2021) - Seastedt, Kenneth P.; Pruett, Nathanael; Hoang, Chuong D.
ABSTRACT: Introduction: Mesothelioma is an aggressive mesothelial lining tumor. Available drug therapies include chemotherapeutic agents, targeted molecular therapies, and immune system modulators. Mouse models were instrumental in the discovery and evaluation of such therapies, but there is need for improved understanding of the role of inflammation, tumor heterogeneity, mechanisms of carcinogenesis, and the tumor microenvironment. Novel mouse models may provide new insights and drive drug therapy discovery that improves efficacy. Areas covered: This review concerns available mouse models for mesothelioma drug discovery and development including the advantages and disadvantages of each. Gaps in current knowledge of mesothelioma are highlighted, and future directions for mouse model research are considered. Expert opinion: Soon, CRISPR-Cas gene-editing will improve understanding of mesothelioma mechanisms foundational to the discovery and testing of efficacious therapeutic targets. There are at least two likely areas of upcoming methodology development. One is concerned with precise modeling of inflammation - is it a causal process whereby inflammatory signals contribute to tumor initiation, or is it a secondary passenger process driven by asbestos exposure effects? The other area of methods improvement regards the availability of humanized immunocompromised mice harboring patient-derived xenografts. Combining human tumors in an environment with human immune cells will enable rapid innovation in immuno-oncology therapeutics.